Preliminary Genomic Characterization of Ten Hardwood Tree Species from Multiplexed Low Coverage Whole Genome Sequencing. - Margaret Staton; Teodora Best; Sudhir Khodwekar; Sandra Owusu; Tao Xu; Yi Xu; Tara Jennings; Richard Cronn; A Kathiravetpilla Arumuganathan; Mark Coggeshall; Oliver Gailing; Haiying Liang; et al. (PLoS ONE, 2015)
Forest health issues are on the rise in the United States, resulting from introduction of alien pests and diseases, coupled with abiotic stresses related to climate change. Increasingly, forest scientists are finding genetic/genomic resources valuable in addressing forest health issues. For a set of ten ecologically and economically important native hardwood tree species representing a broad phylogenetic spectrum, we used low coverage whole genome sequencing from multiplex Illumina paired ends to economically profile their genomic content. For six species, the genome content was further analyzed by flow cytometry in order to determine the nuclear genome size. Sequencing yielded a depth of 0.8X to 7.5X, from which in silico analysis yielded preliminary estimates of gene and repetitive sequence content in the genome for each species. Thousands of genomic SSRs were identified, with a clear predisposition toward dinucleotide repeats and AT-rich repeat motifs. Flanking primers were designed for SSR loci for all ten species, ranging from 891 loci in sugar maple to 18,167 in redbay. In summary, we have demonstrated that useful preliminary genome information including repeat content, gene content and useful SSR markers can be obtained at low cost and time input from a single lane of Illumina multiplex sequence.